Evaluation of ASCE 7 equations for designing acceleration‐sensitive nonstructural components using data from instrumented buildings. (18th December 2017) - Anajafi, Hamidreza; Medina, Ricardo A.
Summary: This study uses instrumented buildings and models of code‐based designed buildings to validate the results of previous studies that highlighted the need to revise the ASCE 7 F p equation for designing nonstructural components (NSCs) through utilizing oversimplified linear and nonlinear models. The evaluation of floor response spectra of a large number of instrumented buildings illustrates that, unlike the ASCE 7 approach, the in‐structure and the component amplification factors are a function of the ratio of NSC period to the supporting building modal periods, the ground motion intensity, and the NSC location. It is also shown that the recorded ground motions at the base of instrumented buildings in most cases are significantly lower than design earthquake (DE) ground motions. Because ASCE 7 is meant to provide demands at a DE level, for a more reliable evaluation of the F p equation, 2 representative archetype buildings are designed based on the ASCE 7‐16 seismic provisions and exposed to various ground motion intensity levels (including those consistent with the ones experienced by instrumented buildings and the DE). Simulation results of the archetype buildings, consistent with previous numerical studies, illustrate the tendency of the ASCE 7 in‐structure amplification factor,  [1 + 2( z / h )], to significantly overestimate demands at all floor levels and the ASCE 7 limit of a p = 2 1 2 to in many cases underestimate the calculated NSC amplification factors. Furthermore, the product of these 2 amplification factors (that represents the normalized peak NSC acceleration) in some cases exceeds the ASCE 7 equation by a factor up to 1.50.